Intragastric injection of botulinum toxin in the treatment of obesity: a single-center study - Hasan Tankut Köseoğlu; Kerem Kenarli; Ahmet Akbay; Çağdaṣ Erdoğan; Alper Macif; Meryem Didem Göktaṣ; Mevlüt Hamamci; Çağdaṣ Kalkan; Firathan Sarialtin; Mahmut Yüksel (Therapeutic Advances in Gastrointestinal Endoscopy, 2024)
Background: In recent years, various novel surgical and non-surgical therapeutic options have been developed for treating obesity. Due to its disputed success, intragastric botulinum toxin A (BTX-A) injection is still being debated. Objectives: We aim to contribute to this controversial issue in the literature by sharing our center’s findings regarding intragastric BTX-A injections in the treatment of obesity. Design: Patients with a body mass index (BMI) of greater than 25 kg/m 2 and at least one obesity-related complication, or a BMI of greater than 30 kg/m 2 without complications, were eligible for the study if they were between the ages of 18 and 65. Methods: Following the same procedure, two endoscopists administered BTX-A to all patients. All patients were evaluated for obesity by measuring their lipid profile, hormone profile, and insulin resistance level before treatment. Results: In our study on 82 patients, we saw a significant mean weight loss (−9.2 kg, p  < 0.001) in the second month, and there was no additional mean weight loss in the sixth month of follow-up. In addition, this result seems to be independent of the patient’s insulin resistance. We did not see any serious side effects in any of the patients. Conclusion: Although the use of intragastric injection of BTX-A in the treatment of obesity is a controversial issue, we showed in our study that it causes significant weight loss. Further studies are needed on this subject, as it can be a safe method when the ideal dose and application site are combined with appropriate patient selection.